Mães de surdos: Concepções em torno da pessoa surda e suas implicações para aquisição/aprendizagem da língua de sinais - Muniz, Joani de Mélo (2016)
The present study is a master dissertation heat, presents an ethnographic qualitative study. We investigate, question and analyze the conceptions al ruit deaf people, built in different social contexts and uttered by mothers of deaf kids. We analyze how those conceptions influence the was in witch mothers work daily with their deaf children, and are related to the process of acquisition/learning of sign language. The study is organized in three chapters. The first one is introductory, where I work the fundamental appointments of which emerged the interest in researching them, in the second chapter we present the methodological perspective and in the last one we present an analytical theoretical discussion around the objectives of this study. Discussion about the conceptions of deficiency and difference are articulated based on authors of Cultural Studies of Education and Deaf Studies, such as Goldfeld (1997), Silva (2000), Skliar (1997, 2005), Perlin (2003), Ladd (2005), Sa (2006), Santana (2007), Lopes (2011), among o hers. The categories of identity and difference are the pillars of discussion, of sign languages. The data show that the abnormality of deaf condition is still predominant in mother's conceptions, although the there are already conceptions that regard deaf people in thru differentiated cultural aspect, which shows a change not only in the characteristics of discourse, but mainly in the practice of everyday relations between mothers and sons and daughters.